Patient Data Processing Information System at the Dolok Masihul Health Center Using the Waterfal Method - Azri Anggara Diva (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2025)
This patient data processing information system is a system for managing patient data and documents including patient identity, examination results and other services that have been provided to patients. As for the patient data processing system and report generation at the Puskesmas, the processing is still manual and still uses bookkeeping media and takes up a lot of space. Therefore, patient care at the Health Center becomes less effective and efficient. By using the website as a tool in data processing, it can facilitate the processing of medical record data and make reports in an easier and more efficient way and can save the space provided. The method used in building this website application uses the waterfall method which starts from analysis, design, coding, testing, implementation and maintenance. Patient data processing information systems play an important role in improving services at the Dolok Masihul Health Center, making it easier for the Health Center to process patient data, visit data, patient medical records and reports.